The Separation of Personal and Business Finances: Accounting Implications for Financial Stability and Transparency in MSMEs in Cipayung District, Depok City - Muhamad Aghil Hanafi; Sasi Ngatiningrum; Astri Arnesia; Istiqomah Nur Hasanah; Nofryanti Nofryanti (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to analyze the importance of separating personal and business finances and its implications for financial stability and transparency among Micro, Small, and Medium Enterprises (MSMEs) in Cipayung District, Depok City. The primary issue faced by MSME owners is a low understanding of basic accounting practices, particularly in segregating personal and business transactions, which leads to inaccurate financial reporting and difficulties in business decision-making. Methodology: This research employed a qualitative approach, with data collection techniques including observation, interviews, and documentation involving MSME owners. Findings: The results indicate that most business owners still mix personal and business finances, resulting in a lack of transparency, difficulty in measuring business performance, and limited access to external funding sources. Financial separation is proven to have positive implications for more systematic financial reporting, increased accountability, and ease of business performance evaluation. Furthermore, the implementation of accounting practices, such as separate transaction recording, the use of dedicated business bank accounts, and the preparation of basic financial statements, can enhance financial stability and external trust. Conclusion: Therefore, continuous education and assistance are required for MSME owners to improve accounting literacy, enabling them to consistently apply financial separation to support business sustainability and growth.